PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA SISWA KELAS V SD - Heru Siddik Nugroho; Rizka Choirul Umam (Elementary School and Education Journal, 2025)
This research aims to develop science learning motivation through the Teams Games Tournament type cooperative learning model in fifth grade students at SD Muhammadiyah Siliran. This research uses a Classroom Action Research (PTK) approach, with a Kemmis & Mc Taggart design consisting of 4 stages, namely: planning, implementation, observation and reflection. The subjects in this PTK were class III of SD Muhammadiyah Siliran, totaling 15 students, consisting of 7 boys and 8 girls. Data collection methods are using observation, questionnaires, interviews and observations. The research results showed that there was an increase in student learning motivation in science subjects. Student learning motivation can be seen from the questionnaire test at the end of the lesson. In Cycle I the percentage reached 73.5% and had not achieved the desired score according to the indicators of success in student learning motivation and in Cycle II the percentage of students' score reached 84.03% and had achieved the desired score or was in accordance with the indicators of success in student learning motivation. exceeds a score presentation of 75%. Based on this, it can be concluded that the Teams Games Tournament type cooperative learning model can increase students' learning motivation in science subjects.